ANALISIS LAPORAN KEUANGAN DALAM MENGEVALUASI KINERJA KEUANGAN PADA PT GAMMA UTAMA SEJATI - IndriHafshari, Khoirunnisa; zulkifli, muhammad ilza; Nurazizah, Neng Sheilla (COMPETITIVE, 2023)
This research was conducted because it has a purpose, namely to measure the financial performance of PT Gamma Utama Sejati. PT Gamma Utama is a company that has the intent and purpose to do business in the field of development and contractors. To achieve this goal, the company has business prospects in the coal and electricity trading sector. This study aims to study and be able to determine the usefulness of financial ratio analysis so that it can determine the company’s financial condition and can assess the performance that has been achieved by the company.. To see the financial condition and see the performance that has been achieved by the company, an analysis can be done using the liquidity ratio, solvency ratio, and profitability ratio. This study uses secondary data that has been previously obtained by researchers and the data is in the form of annual financial reposts at PT Gamma Utama Sejati obtained through the company's internal parties. In conducting this research using a comparative descriptive analysis method which later the annual financial statements that have been previously obtained will be analyzed and the results of the will be compared every year. The financial statements used are financial statements in 2018 and 2019.